Soluble leptin receptor and leptin are associated with baseline adiposity and metabolic risk factors, and predict adiposity, metabolic syndrome, and glucose levels at 2-year follow-up: the Cyprus Metabolism Prospective Cohort Study - Hamnvik, Ole-Petter R.; Liu, Xiamen; Petrou, Michael; Gong, Huizhi; Chamberland, John P.; Kim, Esther H.; Kales, Stefanos N.; Christiani, David C.; Mantzoros, Christos S.; Christophi, Costas A. (My University, 2011)
We examined the relationship between serum levels of leptin-binding protein (soluble leptin receptor [sOB-R]) and leptin with metabolic parameters at baseline and prospectively at 2-year follow-up in young healthy men. A total of 916 eighteen-year-old men were examined at baseline, with a subgroup of 91 participants examined again 2 years later. Anthropometric and metabolic measurements were performed at baseline and at follow-up. In the cross-sectional study, levels of sOB-R were significantly inversely correlated with all baseline measures of obesity and metabolic risk factors (blood pressure, total and low-density lipoprotein cholesterol, and fasting glucose), and significantly positively correlated with high-density lipoprotein cholesterol. After correcting for age, smoking status, and waist-to-hip ratio, the inverse correlation remained statistically significant for all measures of adiposity, fasting glucose, and the metabolic syndrome score. Correlations for leptin were similar in magnitude but opposite in direction to correlations for sOB-R. In prospective analyses, baseline levels of sOB-R were predictive at 2-year follow-up of fasting glucose, the metabolic syndrome score, and measures of adiposity in both unadjusted and adjusted models. Similarly, leptin was predictive of fasting glucose, the metabolic syndrome score, adiposity, and systolic blood pressure. We confirm correlations of leptin and sOB-R levels with measures of adiposity and metabolic risk factors at baseline, and demonstrate for the first time prospectively the role of sOB-R as an independent, although weak, predictor of metabolic syndrome and fasting glucose in young men. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Leptin Receptor; Adiponectin; Ovary Polycystic Disease